2017
DOI: 10.1353/cpr.2017.0046
|View full text |Cite
|
Sign up to set email alerts
|

How Co-Developed Are Community and Academic Partnerships?

Abstract: We present insights that can be used by academic researchers and community leaders looking to co-develop interventions to improve health in urban communities domestically and internationally.JHH in Baltimore, Maryland, is one of the most highly regarded hospitals in the United States. However, its institutional resources stand in marked contrast with those available to the impoverished neighborhoods that surround it. Many have called for JHH to play a greater role in the surrounding community, where it serves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…If you 'involve' your partners, then it is you 'allowing' them to have a role. Instead, your partnership should be one of co-equals where you learn as much from the engagement as they do (Dadwal et al 2017). • It is also important to acknowledge that your partners have extensive expertise that is not related to academic degrees or titles.…”
Section: Do Not Just 'Involve' Your Community Partner In Researchmentioning
confidence: 99%
“…If you 'involve' your partners, then it is you 'allowing' them to have a role. Instead, your partnership should be one of co-equals where you learn as much from the engagement as they do (Dadwal et al 2017). • It is also important to acknowledge that your partners have extensive expertise that is not related to academic degrees or titles.…”
Section: Do Not Just 'Involve' Your Community Partner In Researchmentioning
confidence: 99%
“…Cultivating trust in health systems also contributes to one's access to care, utilization of, and adherence to evidenced based recommendations, thus improving outcomes (17). Trust is also necessary for collaborative decision making and essential for effective and sustainable partnerships (18,19). At a global level, effective trust building in health systems requires accountability to citizens and incorporation of their voices in policies that affect them (1,2,15,20).…”
Section: Introductionmentioning
confidence: 99%
“…By engaging residents early in the process, community planners and public health practitioners can gain a greater understanding of what the community perceives as benefits of a project and allow for resident input to shape the framing, implementation, and outcomes of that project. Research has shown that community engagement may lead to improvements in program design (e.g., scheduling, format, or cultural and linguistic issues), resource development (e.g., funding or partnerships), and uptake of positive health behaviors (e.g., self-management of chronic conditions, reducing exposure to secondhand smoke) (Allen, Colicchio, & Litchman, 2019;Dadwal et al, 2017;McGowan, Musicant, Williams, & Niehaus, 2015;. Engaging with the community may also show respect, build community trust, improve communication, and enhance transparency in how communities work together to create change (Clinical and Translational Science Awards Consortium, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Engaging with the community may also show respect, build community trust, improve communication, and enhance transparency in how communities work together to create change (Clinical and Translational Science Awards Consortium, 2011). Community engagement that incorporates community involvement, shared leadership, and co-development are needed to address the larger issues that affect population health like the social determinants of health, which include social, environmental, economic, and political conditions that impact health (Allen, Colicchio, & Litchman, 2019;Dadwal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation